Subchronic Toxicity of Garcinia Xanthochymus Fruit Bark Extract to Female Rats: Effect on Liver and Kidney - Winata, Hanafis Sastra; Chan, Adek; Diana, Vivi Eulis Diana; Diana, Vivi Eulis; Faradila, Salsa (Asian Journal of Pharmaceutical Research and Development, 2025)
Objective: Garcinia Xanthochymus Fruit Bark has been pharmacologically proven as beneficial as an antidiabetic, antioxidant, detoxifier, and antibacterial agent. Methods: Subchronic toxicity evaluations were performed for 28 days for the control and experimental groups, and for 42 days for the satellite groups. This study employed 30 female white rats, divided into six treatment groups: the control group (Na cmc 0.5%), the test group receiving ethanol extract of kandis tamarind fruit bark at doses of 250, 500, and 1000 mg/KgBW, the control satellite group (Na cmc 0.5%), and the high-dose satellite group (1000 mg/KgBW). Daily observations included toxic symptoms, body weight, mortality, relative organ weight, macropathology, and histopathology of hepatic tissues. Results: The subchronic toxicity test results demonstrated that the ethanol extract of Garcinia Xanthochymus Fruit Bark, administered at a satellite dose of 1000 mg/KgBW, induced toxic symptoms such as weakness and mortality in test subjects by the fourth week, along with significant macropathological changes in the liver marked by white spots. Histopathological analyses of liver and kidney tissues in the test group administered a dosage of 250 mg/KgBW showed no signs of tissue damage. The test group administered doses of 500 and 1000 mg/KgBW, together with the satellite group at 1000 mg/KgBW, had hepatic tissue damage marked by sinusoidal dilation, cellular necrosis, and central venous alterations. Conclusion: The findings showed showed that Garcinia Xanthochymus Fruit Bark can hurt tissues at doses of 500 and 1000 mg/KgBW. The liver tissue damage was shown by changes in central veins, sinusoidal swelling, and cell death.